Exploring Rates of Abnormal Pharmacogenetic Findings in a Pain Practice. (1st March 2014) - Kirsh, Kenneth L.; Ehlenberger, Eric; Huskey, Angela; Strickland, Jennifer; Egan City, Kathleen; Passik, Steven D.
ABSTRACT Pharmacogenetic testing (PGT) is part of increasing efforts to personalize medicine, hopefully leading to better medication selection with more effective, less toxic therapies. Pharmacogenetic testing has relevance for chronic pain treatment, given the frequent comorbidities and polypharmacy. This retrospective study explored the prevalence of polymorphisms in a specialty pain practice in Louisiana. Pharmacogenetic testing was conducted for the cytochrome P450 (CYP) enzymes CYP2B6, CYP2C19, and CYP2D6, or the uridine diphosphate-glucuronosyltransferase 2 family polypeptide B15 (UGT2B15) enzyme utilizing a noninvasive, saliva-based test based on clinical decision-making. The sample consisted of 61 men (58.7%) and 41 women (39.4%), with an average age of 46.7 years (range = 23–83, SD = 11.5 years). Across all tests, 164 (42.3%) were extensive, 99 (25.5%) were intermediate, 28 (7.2%) were ultrarapid, and 27 (7%) were poor metabolizers. Only three patients who had been tested were found to be extensive (normal) for all four genes. These data demonstrate that genetic polymorphisms were frequently encountered. Consideration should be given to obtaining PGT as an aspect of evaluation and treatment planning when working with patients in need of specialty pain consultation and care. Caution is needed, as this brief report encompasses results from a single pain practice in one geographic location with a potentially distinct prevalence of genetic polymorphisms. Further prospective study is needed.